The Landscape as basic Matter of the Project - Giuseppe Di Benedetto (Agathón)
The paper deals with the relationship between architecture and nature through the man-made landscape structural role in a particular project centered on the physical and spiritual dimension of the places. That’s how the landscape is intended as the main purpose of architecture. To explain the conveyed notions, we will examine the results of the design research carried out by the author for his laboratory of architectural design, for his dissertation on Architettura nella roccia about the excavating, subtraction and emptiness design concepts together with the generation of silent architectures.